Strategies for creating the image of a humanist in the “Hodoeporicorum liber unus” (“The Book of Traveling Elegies”) by Jan Rybiński - Mileszczyk, Robert (Melusine. Old Literature and Culture, 2026)
“The Book of Traveling Elegies” by Jan Rybiński is not just a description of the author's journey especially to foreign universities, in order to gain extensive humanistic knowledge, but, and this is probably the most interesting, is also a kind of „visiting card” for the Renaissance intellectual member of the respublica litterarum community. The article presents the methods that Rybiński used to present his person in a subtle and clear way to a new, but also demanding environment of intellectuals gathered in Toruń. The article presents both the pragmatic aspect of this self-presentation, related to the work undertaken by the poet, as well as the purely artistic one, addressed directly to local Toruń humanists.